Pengaruh Pelatihan Asertif Terhadap Keterampilan Sosial Pada Siswa Kelas X Korban Bullying Di SMA N 1 Kamal - Yudho Bawono; Siti Nurfitria; Alifah Rahma Wati (Personifikasi: Jurnal Ilmu Psikologi, 2014)
AbstractBullying is a behavior that is unwanted and aggressive among school-age children where the perpetrator uses physical strength, popularity and blocking access to information to control or hurt another child. This study aimed to determine the effect of assertiveness training on social skills bullied in class X High School. This study is a population with a total study population was all students are victims of bullying in the class X SMA N 1 Kamal. This research is a Pre-Experimental Design with One Group Pretest-Posttest. The research began by distributing a questionnaire to know the students who are victims of bullying in the school that would become the subject of research. Methods of data collection using the attitude scale pre test and post test after receiving training in the form of assertive Social Skills Scale. Data were processed with SPSS 17.0 for Windows statistical test Paired Sample t-Test to determine the effect of assertiveness training on social skills in class X victim of bullying at school N 1 Kamal. The results showed that there was no effect of assertiveness training on social skills in class X victim of bullying at SMAN 1 Kamal. This is partly due to several factors. First in terms of intensity pelati han fairly short, 1 hour per week for 3 weeks. It takes a short time not to change one's behavior. Second, because of the lack of intent or "intention" as a determinant of behavior. Thirdly because the stimulus is given not exceed the original stimulus.